Relevance of Candida and other mycoses for morbidity and mortality in severe sepsis and septic shock due to peritonitis - Lichtenstern, Christoph; Herold, Christina; Mieth, Markus; Brenner, Thorsten; Decker, Sebastian; Busch, Cornelius; Hofer, Stefan; Zimmermann, Stefan; Weigand, Markus A. (Mycoses, 2015)
This single-centre retrospective cohort study evaluated the incidence and outcome of mycoses in critical ill patients (n = 283) with sepsis due to peritonitis. Overall mortality was 41.3%, and the 28-day mortality was 29.3%. Fungal pathogens were found in 51.9%. The common first location was the respiratory tract (66.6%), followed by the abdominal site (19.7%). Candida colonisation was found in 64.6%, and invasive Candida infection in 34.0%. Identified fungi were Candida spp. in 98.6% and Aspergillus spp. in 6.1%. Patients with fungal pathogens showed a higher rate of postoperative peritonitis, APACHE II and tracheotomy. In comparison to patients without fungal pathogens, these patients showed a longer duration on mechanical ventilation, and a higher overall mortality. Patients with Candida-positive swabs from abdominal sites had more fascia dehiscence and anastomosis leakage. Seventy-two patients (48.9%) received antifungal therapy, 26 patients were treated empirically. Antifungal therapy was not associated with a decrease in mortality. Age and renal replacement therapy were associated with mortality. In conclusion, fungi are common pathogens in critically ill patients with peritonitis, and detection of fungi is associated with an increase in overall mortality. Particularly, Candida-positive abdominal swabs are associated with an increase in morbidity. However, we were not able to demonstrate a survival benefit for antifungal therapy in peritonitis patients.